Computer Simulations of Self-Diffusion of Adsorbed Water in a Model for Microporous Portland Cement - Mögel, Hans-Jörg; Wahab, Mirco; Schiller, Peter (Diffusion Fundamentals, 2025)
Microporous cement materials such as some types of Portland cement show swelling and shrinkage with strong hysteresis depending on the humidity. A quantitative theoretical explanation is based on the existence of strong forces mediated by adsorbed water between the pore walls and the resulting elastic response of the solid. We have performed Monte-Carlo simulations of the adsorption equilibrium in the microcapillaries. The microcapillary structure of cementitious materials has been modelled using Tobermorite slit pores. We have found huge pressures and pressure anisotropy within the adsorbed water layers. Accordingly, we obtained self-diffusion coefficients on the surfaces that correspond in magnitude to coefficients in liquid water under high pressure in a three-dimensional bulk volume. Significant differences were observed in lateral diffusion (parallel to the walls) and normal diffusion (perpendicular to the walls). The diffusion kinetics strongly depends on the width of the slit pores. The diffusion coefficients were determined by tracking the mean square displacement of water molecules during the simulations. The pressure and diffusion curves are in accordance with density profiles and radial distribution functions calculated from our simulations.